Show that for non-zero natural numbers k and n. \(\left \{k,n \right \}\subset\left \{ \mathbb{N}\setminus \left \{ 0 \right \} \right \}\)
k⋅(k+1)⋅(k+2)⋅(k+3)⋅...⋅(k+n−1)k\cdot (k+1)\cdot (k+2)\cdot (k+3)\cdot ...\cdot(k+n-1)k⋅(k+1)⋅(k+2)⋅(k+3)⋅...⋅(k+n−1) is divisible by n!n!n!
Note by Jack Han 6 years, 3 months ago
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
_italics_
**bold**
__bold__
- bulleted- list
1. numbered2. list
paragraph 1paragraph 2
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
This is a quote
# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"
\(
\)
\[
\]
2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Let c≡k(modn)c\equiv k (mod\quad { n })c≡k(modn) with 0≤c<n0\le c<n0≤c<n then k+n−ck+n-ck+n−c is a factor in the product. Since c≡k(modn)c\equiv k(mod\quad { n })c≡k(modn), then (k+n−c)(modn)≡(k−c)(modn)≡0(k+n-c)(mod\quad n)\equiv (k-c) (mod\quad n)\equiv 0(k+n−c)(modn)≡(k−c)(modn)≡0 and since one of the factors is divisible by nnn the product must be as well
Log in to reply
k+n−ck+n-ck+n−c is factor if kkk is not a factor.
1≤c<n1\leq c <n1≤c<n
If kkk is divisible by nnn then there is nothing left to prove.
Edit: Also, k+n−c≤k+n−1k+n-c \leq k+n-1k+n−c≤k+n−1
−c≤−1-c \leq -1−c≤−1
c≥1c \geq 1c≥1
Problem Loading...
Note Loading...
Set Loading...
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Let c≡k(modn) with 0≤c<n then k+n−c is a factor in the product. Since c≡k(modn), then (k+n−c)(modn)≡(k−c)(modn)≡0 and since one of the factors is divisible by n the product must be as well
Log in to reply
k+n−c is factor if k is not a factor.
1≤c<n
If k is divisible by n then there is nothing left to prove.
Edit: Also, k+n−c≤k+n−1
−c≤−1
c≥1